Calcein-Modified CeO2 for Intracellular ROS Detection: Mechanisms of Action and Cytotoxicity Analysis In Vitro - Nikita N. Chukavin; Vladimir K. Ivanov; Anton L. Popov (Cells, 2023)
Cerium oxide nanoparticles (CeO2 NPs) are metal-oxide-based nanozymes with unique reactive oxygen species (ROS) scavenging abilities. Here, we studied new CeO2 NPs modified with calcein (CeO2-calcein) as an intracellular ROS inactivation/visualization theranostic agent. The molecular mechanisms of the CeO2-calcein intracellular activity, allowing for the direct monitoring of ROS inactivation in living cells, were studied. CeO2-calcein was taken up by both normal (human mesenchymal stem cells, hMSc) and cancer (human osteosarcoma, MNNG/Hos cell line) cells, and was easily decomposed via endogenous or exogenous ROS, releasing brightly fluorescent calcein, which could be quantitatively detected using fluorescence microscopy. It was shown that the CeO2-calcein has selective cytotoxicity, inducing the death of human osteosarcoma cells and modulating the expression of key genes responsible for cell redox status as well as proliferative and migration activity. Such cerium-based theranostic agents can be used in various biomedical applications.